Disinflation, External Vulnerability, and Fiscal Intransigence : Some Unpleasant Mundellian Arithmetic - Tanner, Evan (IMF Working Papers; Working Paper ;, 2017)
This paper examines the policy challenges a country faces when it wants to both reduce inflation and maintain a sustainable external position. Mundell's (1962) policy assignment framework suggests that these two goals may be mutually incompatible unless monetary and fiscal policies are properly coordinated. Unfortunately, if the fiscal authority is unwilling to cooperate-a case of fiscal intransigence-central banks that pursue a disinflation on a 'go it alone' basis will cause the country's external position to further deteriorate. A dynamic analysis shows that if the central bank itself lacks credibility in its inflation goal, it must rely even more on cooperation from the fiscal authority than otherwise. Echoing Sargent and Wallace's (1981) 'unpleasant monetarist arithmetic,' in these circumstances, a 'go it alone' policy may successfully stabilize prices and output, but only on a short-term basis.